The texture development of ECAP processed AA1050aluminum, before and after a final anneal: effect of the initial texture - Vega, M. C. V. (2014)
Equal Channel Angular Pressing (ECAP) can be used to control deformation and annealing textures. The initial texture has a significant role on texture development and intensity after deformation and anneal. In this work AA 1050 Al samples with different initial textures and initial strain of 0.3 were deformed in a I20° ECAP die. Deformation followed route A, yielding equivalents strains of 1 and 3 above the initial. After ECAP one of the samples was rolled to a thickness reduction of 70%. Texture evaluation was performed by x-ray analysis in the as deformed state and after annealing at 350°C for 1 h, by calculating orientation distribution functions. The microstructure was observed by optical and scanning electron microscopy.